Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/s0377-1237(08)80015-9
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival-Limbal Autograft for Primary and Recurrent Pterygium

Abstract: Conjunctival-limbal autograft is the procedure of choice for primary and recurrent pterygia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…In fact Katircioðlu et al [12], found the graft techniques alone to be as effective as conjunctival autograft with mitomycin C. However, others [13,14], found the recurrence rates of amniotic membrane grafting unacceptably high. The conjunctival limbal auto-grafts have the least recurrence rates as highlighted by Jha et al [15] in this issue.…”
Section: Right To Sightmentioning
confidence: 80%
“…In fact Katircioðlu et al [12], found the graft techniques alone to be as effective as conjunctival autograft with mitomycin C. However, others [13,14], found the recurrence rates of amniotic membrane grafting unacceptably high. The conjunctival limbal auto-grafts have the least recurrence rates as highlighted by Jha et al [15] in this issue.…”
Section: Right To Sightmentioning
confidence: 80%
“…The most common complications of LCAG include pannus at the donor site, conjunctival hyperemia, subconjunctival hemorrhage, conjunctival epithelial defects, and graft retraction [ 38 ]. Conjunctival cysts, symblepharon, and postoperative wound dehiscence are less frequently observed [ 23 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been suggested that 30–50 Gy is the required dose range from a radiation oncology perspective [ 78 ], a high incidence of scleromalacia has been reported after RT. RT alone produces a significant reduction in the size of the pterygium [ 20 , 23 , 57 ]. However, this is usually insufficient for achieving a complete cure, perhaps because it acts on relatively mature tissues, which are less affected by irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Hirst described leaving an intact 1.5 to 2 mm rim of the limbal conjunctiva during dissection of the conjunctival graft and leaving a similar region of bare sclera at the limbus during xation of the graft which will be re-epithelialized by the corneal epithelium. Given the bene ts of limbal stem cell transplantation to the recipient bed especially in the treatment of recurrent pterygia 24,25 , we dissected the graft all the way down to the upper limbus in order to include limbal stem cells.…”
Section: Discussionmentioning
confidence: 99%